Membangun Gereja yang Mendengarkan. Belajar dari Keuskupan Manado - Gregorius Hertanto Dwi Wibowo; Albertus Sujoko; Amrosius Wuritimur (Media: Jurnal Filsafat dan Teologi, 2023)
This article aims to reveal several points regarding the quality of listening in building a synodal Church by learning from listening experiences among the Catholics of Manado Diocese. By using a phenomenological approach, we want to describe the experiences of Catholics in listening interactions in their lives of faith, and how people interpret that experience. The data collection was obtained in conjunction with the focus group discussion process which was carried out in this diocese ahead of the 2023 Synod of Bishops. It was found that both positive qualities and challenges can be found in various communities, lay and clergy, leaders of the people and the people they lead. By carefully appreciating these aspects in the light of Church models, the article provides strategic suggestions for reflection and pastoral action not only in Manado Diocese but also for the wider Church to build a better listening Church.